(3TQM GdcGajIs - (3eMeO Hf GdMSf GdQVj GdCSJQGHGPj , fLe GdOjf,J (B686 (3g` s ((3GdbGgQI s)
(3ChdgG (B:s
(3GdcdeI daX hVY deYfi eaQO, CYde Cf GdTGQY aj Yde ef GdYdhe dGHO Cf jYde ChdkG ef Pdc GdYde KdGKI CTjGA s
(3BNQgG (B:s
(3cbhdc aj GVQHf GVQHG jYfj JbdH Gdfhf GdNajaI EPG GfaJM eG bHdgG CdakG ceG JbOe BfakG hGdMeO ddg s
(3HChd GdeNWhWI Gfg GdYGajI ai TQM GdcGajI dEeGe GdMQejf hai agQS OGQ GdcJH GdeUQjI Gfg caGjI GdYGajI ai TQM GdcGajI hGfg djS dEeGe GdMQejf GdeYQhas
(3hde jTQ cTa GdXfhf Edi gPG GdTQMs
(3HChdgG Jedc eDQN aj (B1023(3g`` s
(3hHgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdfMhs